Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Karet Di Kabupaten Sarolangun - Sabyan, Sabyan; Wiarta, Iqra (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
Agriculture in Indonesia has an important role in development, including in Jambi Province, where most of the population lives in rural areas and depends on the agricultural sector. However, there is still a problem of economic inequality between rural and urban areas, especially related to income. This study was conducted in Sarolangun Regency to examine economic growth and per capita income. The data shows an increase in per capita income from 2005 to 2006. The plantation sector, especially rubber, has an important role in the economy of Sarolangun District. The research method used was a survey with primary and secondary data collection. The sample consisted of 40 rubber farmers. The analysis included farmers' socioeconomic characteristics, such as age, education, number of family members, and farming experience. The results showed that the majority of farmers were of productive age, with a low level of education. The number of family members affects income levels, and farming experience also plays an important role. Constraints faced by farmers include traditional land management and weather impacts. Farming costs, especially labor costs, affect income. Net income per hectare of rubber land varies depending on productivity and prices. Efforts are needed to increase productivity and overcome constraints faced by farmers to improve their welfare